Effect of Meteorological Conditions on Storability of the Scab-Immune Columnar Apple Varieties - Nikitin A.; Makarkina M. (Техника и технология пищевых производств)
Introduction. Weather conditions during vegetative period have an effect on the duration of fruit storage, as well as the yield of commercial fruits unaffacted by physiological disorders or microbiological diseases. In this regard, new apple varieties demand a detailed study of economic and biological indicators, determination of storage period, and various factors that may affect it. Study objects and methods. The research featured preservation capacity of five new scab-immune columnar apple varieties cultivated at the All-Russian Research Institute for Fruit Crop Breeding (Orlov Region, Russia), namely ‘Vostorg’, ‘Zvezda’ ‘Efira’, ‘Poezia’, ‘Priokskoye’, and ‘Sozvezdiye’. The apples were stored in an industrial refrigerator at +2°C. The Selyaninov’s hydrothermal coefficient (HTC) was used as a predictive indicator of the potentially effective storability. Results and discussion. A set of experiments was conducted to determine the effect of the weather conditions during the vegetative period on the yield of commercial fruits. The best preservation was recorded for the fruits harvested in the years with sufficient rainfall during the growing season. The most comfortable conditions of seasonal humidification for the long-term storage of fruits were formed for ‘Zvezda Efira’ and ‘Sozvezdiye’ in 2014 and ‘Poezia’ and ‘Priokskoye’ in 2016 at HTC = 1.0. The storability depended on the weather conditions during the growing season and the variety. The ‘Sozvezdiye’ variety showed the highest commercial yield after storage in 2014 (96.7%), while the lowest commercial yield (64.2%) belonged to the ‘Vostorg’ apples in 2016. ‘Sozvezdiye’ had the highest effective persistence of commercial fruits (83.6–96.7%) during the whole study period (92.0% on average). ‘Vostorg’ and ‘Poezia’ demonstrated worse results than other varieties (76.2% and 76.8% on average, respectively). Conclusion. Poor precipitation and excess heat in the period of 30 days before harvesting adversely affected the fruit storability, which led to scald. ‘Zvezda Efira’ and ‘Sozvezdiye’ were absolutely stable to scald. The dry year of 2012 had a positive effect on the apples as the level of ascorbic acid increased during storage (82.8% of the baseline). Therefore, it is advisable to use HTC to predict fruit quality and storage period.